Signatures of induced superconductivity in AlOx-capped topological heterostructures. (May 2019) - Schüffelgen, Peter; Rosenbach, Daniel; Pang, Yuan; Kampmeier, Jörn; Luysberg, Martina; Kibkalo, Lidia; Mussler, Gregor; Veldhuis, Dick; Brinkman, Alexander; Lu, Li; Schäpers, Thomas; Grützmacher, Detlev
Highlights: Fabrication of S-TI-S junctions from in situ capped topological heterostructures. Fraunhofer-like patterns indicate transport via coherent Andreev states. Transmission electron microscopy confirms a crystalline and capped weak link. Abstract: In order to access exotic Dirac and Majorana states in (Bi, Sb)-based topological insulators (TIs), the physical surface of those crystals should not be exposed to air. 2–3 nm of in situ deposited Al on top of pristine TI thin films immediately oxidizes after taking the sample to ambient conditions. The native AlOx provides a favorable hard capping, which preserves the topological surface states during ex situ device fabrication. Here, we present a process on how to construct superconductor – topological insulator – superconductor (S-TI-S) junctions from in situ capped thin films comprised of 15 nm Sb2 Te3 on top of 6 nm Bi2 Te3 . The thicknesses of the Sb2 Te3 and the Bi2 Te3 layer allow us to precisely tune the Fermi level of the upper surface of the Sb2 Te3 layer. The challenge is to provide a transparent interface between Sb2 Te3 and the superconductive Nb, while assuring an AlOx -capped weak link in between two closely separated Nb electrodes. Low temperature experiments on our junctions provide evidence for charge transport mediated by coherent Andreev states. Magnetic field dependent measurements yielded Fraunhofer-like patterns, whose periodicities are in good agreement with the effective areas of the respective junctions. Transmission electron micrographs of the narrowest junction confirm a crystalline and capped weak link. Our results provide the first reported signatures of induced superconductivity in S-TI-S junctions, which are capped by native AlOx . The presented process allows for accessing S-TI hybrid devices via magnetic flux, while assuring in situ conserved weak links. This makes as-prepared junctions a promising platform for proposed flux-controllable Majorana devices.